Etika Komunikasi Dakwah Qaulan Baligha dalam Dakwah Habib Ja’far pada Program Log In di Kanal YouTube Deddy Corbuzier dan Respon Warganet terhadap Programnya - Fujia Mesarina Sasmita; Bambang Saiful Ma’arif; Nia Kurniati (UNISBA Press, 2024)
Abstract. Habib Ja’far is a preacher (da’i) who appears on the “Log In” program on Deddy Corbuzier’s YouTube channel. This research aims to understand the communication ethics of Qaulan baligha preaching, classify netizens’ responses, examine the application of Qaulan Baligha by Habib Ja’far, and analyze netizens’ responses to the communication ethics of Qaulan Baligha preaching. A descriptive analysis was conducted using a qualitative approach with content analysis method. The data were analyzed using Krippendorff’s analysis and the types of responses according to Steven M. Chaffe. The results are as follows: First, according to scholars, Qaulan Baligha is a form of speech that is impactful and touches the heart, contains wisdom, and eloquence, and is easily understood. Second, netizens’ responses to the “Log In” program were classified based on posiive and negative formats, as well as affective, cognitive, and conative response type. Third, Habib Ja’far implemented Qaulan Baligha in his preaching, which was predominantly characterized by eloquence. Fourth, netizens’ responses demonstrated the communication ethics in Qaulan Baligha preaching. Abstrak. Habib Ja’far merupakan sosok da’i yang mengisi Log In di kanal YouTube Deddy Corbuzier. Tujuan penelitian ini mengetahui etika komunikasi dakwah qaulan baligha, klasifikasi respon warganet, penerapan qaulan baligha oleh Habib Ja’far, respon warganet terhadap etika komunikasi dakwah qaulan baligha. Penelitian deskriptif analisis menggunakan pendekatan kualitatif dengan metode analisis isi. Data dianalisis dengan analisis Krippendorff dan jenis-jenis respon menurut Steven M. Chaffe. Hasil penelitian: Pertama, menurut para ulama qaulan baligha adalah perkataan yang berbekas dan menyentuh hati, mengandung hikmah, kefasihan berbicara, serta mudah dimengerti. Kedua, respon warganet terhadap program Log In diklasifikasikan berdasarkan format respon positif dan negatif, serta jenis respon afektif, kognitif, dan konatif. Ketiga, Habib Ja’far menerapkan qaulan baligha dalam dakwahnya yang didominasi dengan unsur kefasihan berbicara. Keempat, respon warganet menunjukkan etika komunikasi dakwah qaulan baligha.